Utilization of Digital Technology for Enhancing Creative Performance in the Resilient Community of Strategic Partners of Sembangin Service Cooperative Metawork Community: Pemanfaatan Teknologi Digital untuk Peningkatan Kinerja Kreatif pada Komunitas Tangguh Mitra Strategis Koperasi Jasa Sembangin Community Metawork - Aggry, Aggry Saputra; As Saidah, Muthiah; Rahmad, Abdul; Zulfachmi, Zulfachmi; Zulkipli, Zulkipli; Rahayu, Vita (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2025)
Perkumpulan Keluarga Berencana Indonesia (PKBI) is a non-governmental organization that leads the Family Planning movement in Indonesia, focusing on families as pillars of health, education, and welfare. PKBI Riau Islands region supports resilient communities, including the Sehati Business Group Community, Peer Educators, and Community Cadres, through the Sembangin Community Metawork Service Cooperative for economic empowerment. Several challenges faced by the community cadres include administrative efficiency, creative design, and file management, necessitating the use of digital technology to address these issues. The results of this community service program show an improvement in the community’s skills in using computers, office applications, Canva design, and cloud management. The community cadres are now able to manage administration and files more efficiently, as well as produce more creative design materials